(untitled) (The Review of Diabetic Studies, 2024)
This growing burden of asthma and allergic disorders in Saudi Arabia is an important public health issue, but a thorough appreciation of the exact, manipulable environmental risk determinants to this phenomenon in the local urban environment is a knowledge gap. This research was thus in a bid to establish the prevalence of these conditions and measure the independent relationships of the key exposures, including culturally common practices, to inform specific interventions. The study was a cross-sectional study done on a multi-stage stratified random population of 750 adults in Riyadh, Jeddah, and Dammam. The results of health outcomes, environmental exposures, and lifestyle factors were gathered through a validated questionnaire and were analyzed in terms of chi-square tests and multiple logistic regression. Asthma was diagnosed by doctors in 16.3%. Having a family history of atopy (adjusted odds ratio, AOR=4.02; 95% CI: 2.673604; p=0.001), living within 100 meters of heavy traffic (AOR=2.41; 95% CI: 1.56372; p=0.001), and being a frequent user of Bakhoor (incense) at home were significant independent risks of asthma after confounding (p=0.002). The research finds that a complex interplay of unalterable genetic susceptibility and of strong, culture-specific, environmental exposures causes the epidemiology of respiratory disease in urban Saudi Arabia. This offers a crucial evidence foundation to population health initiatives to reduce traffic-related air pollution and indoor combustion products, as well as enhancing the chronic disease management systems.